Nuclear encoded photosynthesis genes are specifically controlled by the NuA4 complex - Bieluszewski, Tomasz; Sura, Weronika; Bieluszewska, Anna; Kabza, Michal; Abram, Mateusz; Wlodzimierz, Piotr; Dziegielewski, Wojciech; Szymanska-Lejman, Maja; Lachance, Catherine; De Winne, Nancy; De Jaeger, Geert; Cote, Jacques; et al. (bioRxiv, 2019)
NuA4, an essential histone acetyltransferase complex, is required for efficient transcription in eukaryotes. Using genome editing, genomic approaches and biochemical assays, we characterized plant homologues of two key components of this complex, EPL1 and EAF1 in Arabidopsis thaliana. Surprisingly, we found that loss of AtEPL1, which is necessary for enzymatic activity of NuA4, is not lethal. Contrary to yeast, mutants lacking AtEAF1, responsible for complex targeting, display severe pleiotropic phenotype which copies that of Atepl1. Atepl1 and Ateaf1 mutants grow slowly, contain reduced chlorophyll levels and small chloroplasts. We provide evidence that these alterations are not caused by disturbance of GLK transcription factors, the major regulators of chloroplast development. Using ChIP-seq we show that H4 acetylation levels are dramatically reduced in the chromatin of the Atepl1 mutant, while H3 acetylation remains mostly unchanged. We use our data to define NuA4-dependent genes and show that chloroplast-related genes are significantly overrepresented in this group, consistent with the pale-green phenotypes of the mutants. We propose that NuA4 was adopted in plants to control nuclear-encoded photosynthesis genes.